Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1021/ic8010184
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ZSM-5 Zeolite Confinement on Reaction Intermediates during Dioxygen Activation by Enclosed Dicopper Cations

Abstract: We investigate how nanospaces surrounded by a 10-membered ring of ZSM-5 zeolite affect the reaction intermediates formed during dioxygen activation by enclosed dicopper cations. Two types of dioxygen intermediates are considered: one is an O(2)...Cu(2) complex, where dioxygen binds to the two Cu cations, and the other is a bis(mu-oxo)dicopper complex converted from an O(2)...Cu(2) complex by the cleavage of the O-O bond. We employ large-scale density functional theory (DFT) calculations with the B3LYP function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
71
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 91 publications
11
71
1
Order By: Relevance
“…When a transition metal atom is embedded in a nanometer-scale cavity of a host, the interactions with a guest unsaturated hydrocarbon can be further affected by host confinement. The confinement effects on the inner bond formation have been well discussed in our recent theoretical studies [11,12,13,14,15,16]. In particular, we found various types of binding of a guest molecule into copper cations enclosed in the restricted environment of a ZSM-5 zeolite [14,15,16].…”
Section: Introductionsupporting
confidence: 57%
“…When a transition metal atom is embedded in a nanometer-scale cavity of a host, the interactions with a guest unsaturated hydrocarbon can be further affected by host confinement. The confinement effects on the inner bond formation have been well discussed in our recent theoretical studies [11,12,13,14,15,16]. In particular, we found various types of binding of a guest molecule into copper cations enclosed in the restricted environment of a ZSM-5 zeolite [14,15,16].…”
Section: Introductionsupporting
confidence: 57%
“…Previously, our studies confirmed that this B3LYP-optimized MFI zeolite model comprised of 10-MR in cavities reproduced well the experimentally observed data. [12][13][14]22,[24][25][26][27][28][29][30][31] Taking our previous studies into consideration, we used the M7 site for the Al substitution position; 32 and we defined the Al configuration as the [M7-S2] arrangement. [12][13][14]30 To optimize fully the larger MFI geometry with a 10-MR cavity, we used the 6-311G(d) basis set for the zinc atom and the 6-31G (d) basis set for the Al atom, as well as four O atoms that were connected to the substituted Al atom.…”
Section: Computational Methodology (Calculation Method)mentioning
confidence: 99%
“…From the calculations of Yumura et al . both side-on peroxo and bis(μ-oxo) dicopper cores were found to be energetically favorable in the 10MR of ZSM-5 91. In the work of Goodman et al .…”
Section: Activated Oxygen On Tmi and Its Reactivitymentioning
confidence: 96%